Estrogen deficiency induces bone loss by increasing T cell proliferation and lifespan through IFN-γ-induced class II transactivator - Cenci, Simone (National Academy of Sciences, 2003)
Expansion of the pool of tumor necrosis factor (TNF)-α-producing T cells is instrumental for the bone loss induced by estrogen deficiency, but the responsible mechanism is unknown. Here we show that ovariectomy up-regulates IFN-γ-induced class II transactivator, a multitarget immune modulator, resulting in increased antigen presentation by macrophages, enhanced T cell activation, and prolonged lifespan of active T cells. Up-regulation of class II transactivator derives from increased production of IFN-γ by T helper 1 cells, resulting from enhanced secretion of IL-12 and IL-18 by macrophages. The resulting T cell expansion and bone loss are prevented in vivo by both blockade of antigen presenting cell-induced T cell activation, and silencing of IFN-γ receptor signaling. Thus, increased IFN-γ-induced class II transactivator expression and the resulting enhanced T cell proliferation and lifespan are critical to the bone wasting effect of estrogen deficiency.